Modulated magnetic and piezoresponse phase by applied electric field in 2D layered materials at room temperature - Joong Yeon Lim; Seonghwan Kim; Young-Seong Kim (Results in Physics, 2025)
A hybrid perovskite material with a Two-dimensional (2D) layered (C4H9NH3)2PbIBr3 crystal structure is presented that exhibits magnetoelectricity and piezoelectricity coupling properties at room temperature. The interaction between ferromagnetism and piezoelectricity was achieved by harmonizing their respective ferroic orders. 2D layered organic–inorganic hybrid perovskites demonstrated controlled multifunctional ferroic attributes, with each characteristic established. The magnetic and piezoresponse phase rotation was controlled by modulating the electric-field strength using the magnetoelectricity and piezoelectricity. The responsive and phase-controllable behavior of ferromagnetism and piezoelectricity in 2D hybrid perovskites was effectively managed by an external electric field induced by the coupling between ferroic orders at room temperature. This discovery offers a promising avenue for future research on hybrid perovskites with novel 2D layered-crystal structure.